2004
DOI: 10.2166/wst.2004.0004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of a paper mill wastewater treatment plant using UV/VIS spectroscopy

Abstract: A submersible UV/VIS spectrometer was used to monitor a paper mill wastewater treatment plant. It utilises the UV/VIS range (200-750 nm) for simultaneous measurement of COD, filtered COD, TSS and nitrate with just a single instrument. The instrument measures in-situ, directly in the process. Paper mill wastewater shows typical and reproducible spectra at various process measuring points. There is a relative maximum at 280 mm due to the absorbance by dissolved organic substances, mainly ligninic acids. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 4 publications
1
31
0
8
Order By: Relevance
“…Measures to remove color from the effluent of P&P mills have been reviewed and reported (Bajpai and Bajpai 1994;Garg and Tripathi 2011;Garg et al 2012). Langergraber et al (2004) discussed the evaluation of color in such wastewater by instrumental methods. …”
mentioning
confidence: 99%
“…Measures to remove color from the effluent of P&P mills have been reviewed and reported (Bajpai and Bajpai 1994;Garg and Tripathi 2011;Garg et al 2012). Langergraber et al (2004) discussed the evaluation of color in such wastewater by instrumental methods. …”
mentioning
confidence: 99%
“…Los valores del espectro se encuentran entre 200 nm y 750 nm de longitud de onda, con intervalos de 2,5 nm [9]. El análisis que se presenta a continuación se realizó para las series de tiempo de espectros de absorbancia compuestas por 5705 registros en cada sitio de muestreo: (i) para PTAR-Salitre (Bogotá D.C.) del 29 de junio de 2011 a las 09:03 h al 3 de julio de 2011 a las 17:33 h (una muestra por minuto); (ii) para la Estación Elevadora de Gibraltar (EEG) del 18 de octubre de 2011 a las 11:08 h al 22 de octubre de 2011 a las 15:21 h (una muestra por minuto) y (iii) PTAR San Fernando de 24 de septiembre de 2011 a las 06:04 h a 2 de octubre de 2011 a las 9:16 h (una muestra cada dos minutos) como se observa en la Figura 1.…”
Section: Captores Uv-visunclassified
“…In order to identify specific groups of compounds based on recent studies reported in the literature (Thomas et al, 1996;Çeçen, 1999;Arslan-Alaton et al, 2002;Langergraber et al, 2004;Chamorro et al, 2005;Lunidquist et al, 2007), a scan was performed of the UV-VIS spectrum between 200 and 346 nm. Çeçen (1999) proposed the use of the following wavelengths and ratios: VIS 346 for lignosulphonic acids; UV 254 for aromatic compounds; UV 280 for lignin derivatives, and the relationships VIS 346 /CODd and UV 280 /CODd.…”
Section: Physicochemical Analysismentioning
confidence: 99%